Special Considerations for Tympanoplasty Type I in the Oncological Pediatric Population: A Case-Control Study - Richard, Celine; Baker, Emily; Wood, Joshua (Frontiers in Surgery, 2022)
Introduction: Although cutting-edges antineoplastic therapies increase survival in children with malignancies, the optimal surgical strategy to address associated comorbidities such as chronic tympanic membrane perforation is still poorly documented. The aim of this study is to evaluate the outcomes of type I tympanoplasty in pediatric cancer survivors who received chemo and/or radiotherapy to the skull and to identify potential associated risk factors. Methods: Case-control study including medical records review of oncologic patients (age <21) treated at the same Academic medical oncologic center between March 2015 and July 2021. Patients and middle ear status related variables were analyzed, and outcomes were compared with matched peers without any history of malignancies. Results: 7 pediatric cancer survivors and 7 paired children without any history of malignancies, were included in this report. The mean age at tympanoplasty type I surgery was 10.2 and 10.1 years in the oncologic and control group respectively. Three pediatric cancer patients had received chemotherapy alone, one patient had radiotherapy to the skull base and 3 patients had chemoradiotherapy. Tragal perichondrium with cartilage was used in most of the pediatric cancer survivor cases (4 out 7 cases) while xenograft and Temporalis fascia without cartilage graft were used in 5 out of the 7 control cases. Rate of tympanic membrane perforation recurrence was similar between groups (28.6%). Mean functional gain for AC PTA was 2.6 dB HL and 7.7 dB HL for the oncologic and control group respectively. Mean postoperative ABG was 10.7 dB HL (median = 8.7; IQR = 13.8) for the oncologic cohort and 10.1 dB HL (median = 10.7; IQR = 9.6) for the control group. Discussion: Although healing abilities and immunological defenses are compromised as part of the expected effects of antineoplastic therapies, type I tympanoplasty can be safe and effective in this population. In our experience, we would recommend the procedure to be performed at distance (> 1.2 years) from treatment completion and include cartilage as part of graft materials. While different approaches may be considered, otoendoscopy showed excellent results with less morbidity in this vulnerable population.